Hole, impurity and exciton states in a spherical quantum dot - V.I. Boichuk; I.V. Bilynskyi; R.Ya. Leshko (Condensed Matter Physics, 2010)
The 3x3 kp hole Hamiltonian for the wave-function envelopes (effective mass Hamiltonian) was used for calculation of discrete states of the hole and acceptor hydrogenic impurity in a spherical Si/SiO2 nanoheterostructure as a function of the quantum dot radius by neglecting the corrugation of constant-energy surfaces. A study was conducted in the case of finite potential well at the separation boundary of the nanoheterosystem. The dependence of the hole energy spectrum on polarization charges, which arise at the separation boundary of the media, and on the dielectric permittivity, was defined. Using the exact electron and hole solutions, the exciton wave-function was constructed and the exciton ground-state energy was defined. The theoretical results have been compared with experimental data.